Hindi to Punjabi machine translation system based on statistical approach. Issue 4 (4th July 2018) - Kumar, Ajit; Goyal, Vishal
Abstract: Machine Translation problem is an open area of research. It is a challenge to build a domain independent, effective and efficient MT System. The major approaches to machine translation encountered in literature are Word-for-Word Translation, Syntactic Transfer, Semantic Transfer, Interlingua Approach, Example Based Translation, and Statistical Approach to Translation. The existing Hindi to Punjabi MT systems have been developed using rule bases approach and word-for-word translation approach. The present paper is an attempt to study the Architecture of Hindi to Punjabi MT System based on Statistical Approach.